Comparison of Clinical and Radiological Results in Robotic-Assisted and Traditional Total Knee Replacement: A Comprehensive Systematic Review - Christian; Stefanie (The International Journal of Medical Science and Health Research, 2024)
Background: Robotic-assisted total knee arthroplasty (RATKA) enhances surgical precision and prosthesis alignment compared to conventional total knee arthroplasty (COTKA), potentially improving outcomes and patient satisfaction for knee osteoarthritis. Methods: The review adhered to PRISMA 2020 standards and analyzed full-text English literature from 2014 to 2024. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of  500 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, ten articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: RATKA demonstrates superior radiological alignment and precision compared to COTKA, while achieving comparable functional outcomes and complication rates. The integration of robotic technology in orthopedic surgery holds promise, yet ongoing research is crucial to optimize its clinical application and enhance patient outcomes globally.